Vitamin E nanoparticles enhance performance and immune status of Nile tilapia - Enas A. H. Farag; Mohamed Z. Baromh; Naglaa El-kalamwi; Ahmed H. Sherif (BMC Veterinary Research)
Abstract Vitamin E (VE) is an essential vitamin liposoluble antioxidant in aquatic animals that is usually lost during feed processing and digestion, whereas nano-chitosan, a polysaccharide, could protect VE. In this study, Nile tilapia (70.85 ± 0.2 g) was fed VE (100 mg/kg dry diet) and a chitosan protected-VE nanoparticle (NPs) with gradual percentages of recommended dose 25%, 50%, 75%, and 100% for 4, 6, and 8 weeks. Growth parameters total weight gain (TG), daily weight gain (DWG), and relative growth rate (RGR) were significantly and positively correlated with VENPs additions. Regardless of the addition level, the feed conversion ratio (FCR) was significantly lower in the VENP groups. Lysozyme, serum antibacterial activity, and oxidative burst activity indicated the superiority of VENPs (VENPs75 and VENPs100) in enhancing the fish’s innate immunity compared to bulk VE and the control groups. Fish were experimentally challenged with pathogenic Aeromonas hydrophila; those received dietary showed a low mortality rate (MR%), about 40% compared with 70% in the control with lower re-isolation compared to the control and VE groups. VENPs could provide ascending relative protection level during the period of 4 to 8 weeks; RPL ranged from 33.3 to 42.86% (VENPs100), 16.67–42.86% (VENPs75), 0 to 28.57% (VENPs50), and 0 to 14.29% (VENPs25 and VE), respectively. Finally, this study recommended incorporating VENPs into the Nile tilapia diet at 50, 75, and 100 mg/ kg fish feed. Fish in the VENPs75 and VENPs100 groups were immune boosted, becoming less vulnerable to A. hydrophila infection.